2023
DOI: 10.1371/journal.pone.0284725
|View full text |Cite
|
Sign up to set email alerts
|

Elite lean athletes at sports high schools face multiple risks for mental health concerns and are in need of psychosocial support

Abstract: The combined demands on an adolescence in an elite sports high school can negatively affect mental health (eg, stress, burnout, depression, anxiety). Late adolescence is also when elite-striving athletes typically transition from junior-to-senior level programs. In addition, adolescent elite lean sports athletes have an increased risk of suffering from abnormal eating pathology. The purpose of this study was to investigate the perceived psychosocial needs that young, elite-striving lean sports athletes in spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…36 This life period also coincides with the age for junior-to-senior transition in sports, which can add additional sports-related stressors on adolescent athletes. 16 In this study we found direct relationships between sleeping problems/fatigue, perceived pressure/activation and indicators of poor general mental health, with higher scores reported in older age groups. The results suggest that societal changes and general stressors in everyday life affect adolescent athletes, such as the general population.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…36 This life period also coincides with the age for junior-to-senior transition in sports, which can add additional sports-related stressors on adolescent athletes. 16 In this study we found direct relationships between sleeping problems/fatigue, perceived pressure/activation and indicators of poor general mental health, with higher scores reported in older age groups. The results suggest that societal changes and general stressors in everyday life affect adolescent athletes, such as the general population.…”
Section: Discussionsupporting
confidence: 47%
“…Emerging evidence shows that participation in organised sports can protect adolescents’ mental health and help develop positive health behaviours. 16 17 Panza et al 18 observed a weak yet significant negative association between sports involvement and self-reported anxiety and depression among athletes aged 10–20. Likewise, Rodriguez-Ayllon et al 19 found a weak but significant relationship between physical activity and positive mental health among adolescents but no significant relationship for children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, elite athletes, who had better access to support, demonstrated a notably higher resilience to disruptions caused by the pandemic [ 46 ]. From the psychosocial perspective, athletes’ mental health is affected by social support, psychological safety, communication, and self-behaviors [ 47 ]; thus, the involvement of family members (i.e., parents and siblings), coaches, teammates, may play a substantial role in regulating or reducing stress [ 47 ]. Likewise, keeping athletes informed about available psychological-related services (screening, consultation, etc.)…”
Section: Discussionmentioning
confidence: 99%